The Role of the Distributor Network in the Persistence of Legal and Ethical Problems of Multi-level Marketing Companies - Groß, Claudia (Journal of business ethics, 2019)
Multi-level marketing companies (MLMs) such as Amway, Herbalife, or Tupperware differ from most other companies. They market their products and services by means of self-employed distributors who typically work from home, sell products to end consumers, and recruit, motivate, and educate new distributors to do the same. Although the industry’s growth seems to illustrate the attractiveness of MLMs, the industry has been facing several legal and ethical problems. In this paper, we focus on these problems and argue that an extended MLM model may help us to understand why such problems continue to occur, despite the countermeasures that have been implemented. By explicating how problems relate to a specific but often overlooked characteristic of MLMs, i.e., the so-called distributor network, we provide an extended understanding of (a) MLMs’ mode of operation, (b) the sources of their legal and ethical problems, and (c) the reason that currently implemented and suggested countermeasures may not suffice. Moreover, based on our extended understanding of MLMs and their problems, we propose additional countermeasures.